2004
DOI: 10.1159/000081517
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Serum Pepsinogen II in the Management of <i>Helicobacter pylori</i> Infection

Abstract: Background: Serum pepsinogen II (sPGII) levels are known to increase during Helicobacter pylori infection. Aim: To assess H. pylori infection and success of H. pylori therapy by means of sPGII levels. Methods: sPGII levels were determined in 156 H. pylori-positive and 157 H. pylori-negative consecutive patients with dyspeptic symptoms. Additionally, sPGII determination was performed in 70 H. pylori-positive patients 2 months after H. pylori eradication therapy. In 29 of these 70 patients, gastroscopy was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The difference between sPGI and sPGII could be explained by the gastric site of constitution; the first one is produced only in the corpus glands, while the latter in both the antrum and corpus, and consequently relating to gastric inflammation independently of its localization. In our previous study, indeed, performed in 70 H. pylori-positive dyspeptic adult patients [35] , sPGII increased significantly in comparison to H. pylori-negative ones and successful H. pylori eradication was followed by a significant reduction of both of these parameter levels and gastric mucosa neutrophilic infiltration.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The difference between sPGI and sPGII could be explained by the gastric site of constitution; the first one is produced only in the corpus glands, while the latter in both the antrum and corpus, and consequently relating to gastric inflammation independently of its localization. In our previous study, indeed, performed in 70 H. pylori-positive dyspeptic adult patients [35] , sPGII increased significantly in comparison to H. pylori-negative ones and successful H. pylori eradication was followed by a significant reduction of both of these parameter levels and gastric mucosa neutrophilic infiltration.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, the cross-combination of IgG-Hp ؒ sPGII product and IgG-Hp antibodies can reliably diagnose or exclude the presence of H. pylori chronic gastritis. These non-invasive serological tests are less stressful for children if compared to endoscopy or UBT, and could be proposed in the initial management of children with upper gastrointestinal symptoms as well as in monitoring H. pylori eradication, if the satisfactory result observed in adults [35] will be extended in children. These results need to be confirmed in a larger cohort, also stratifying children in different age classes in order to perform the appropriate cutoff parameters before recommending their widespread clinical application as non-invasive first-pass markers of gastric disease in a pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because pangastritis might play a role in gastric ulcer, gastric atrophy, and gastric cancer, we further suggested a cut-off value of 11.8 µg/l with 85.5% NPV. The clinical use of this marker is limited due to its low PPV but it might be helpful to be applied in combination with other markers in multistep screening programs, however it is suggested that PGII <9.47 µg/l [35] or one fourth decrease in PGII level [36] could be used as a marker for H. pylori eradication. Furthermore, using PGII cutoff value in addition to PGI could help to make a more homogenous group for epidemiologic studies of atrophy association with other gastrointestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…None of them took clopidogrel or warfarin, and underwent to upper GI endoscopy with biopsy: histopathology confirmed that all patients having serological values according to OGA had OGA (two having OLGA III and one having OLGA IV staging); iii) 10 patients had serological values according to antral gastritis, nine of them with atrophy, that do not influence gastric secretion. 6,10 Twenty-one out of 25 patients (84.0%) had serological values according to H. pylori infection (IgG against H. pylori >30 EIU). Due to the age of our population, no further investigation on current H. pyloristatus were performed.…”
Section: Resultsmentioning
confidence: 99%